Efficiency comparison of ESAs and IMDPA models in evaluation and mapping of desertification status (a case study in Boushehr Province, SW Iran) - Bahreini, Fatima; Fakhri, Farhad (Scientific Journal of Environmental Sciences, 2014)
Desertification is the consequence of processes in which climate change and human activities are the most effective factors in arid and semi-arid regions, especially in a major part of Iran. The present study aims to quantitatively assess the desertification situation based on ESAs (Environment Sensitive Areas to Desertification) and IMDPA (Iranian Model of Desertification Potential Assessment) models in southwest of Iran. IMPDA model considers five indicators such as climate, soil, vegetation, erosion, water resources as main coefficients to evaluate the desertification situation. ESAs model takes the physical environment and land management characteristics such as soil, vegetation, climate, and land management for classification of desertification intensity. These layers were extracted and manipulated from the available topographic map data, geologic map, satellite image, and field survey data analyses. Spatial analyst function in ArcGIS software was used for matching the thematic layers and assessing the desertification index, of which the map of environmentally sensitive areas of study area is produced. Based on the results obtained from the IMDPA model, %49.11 of the study area is classified as severe desertification class, and %49.89 in moderate class, and quantitative value of desertification intensity for whole the study area was obtained as [1]DSI =1.55 that is indicative of average desertification intensity in the region. Based on the results obtained from ESAs method, %3.87 of the study area is classified as the fragile class (F2), %38.78 in the average critical (C2) and also nearly %56.42 in the severe critical class (C3). The comparison results show that the IMDPA model have better performances in evaluation current desertification status from ESAs model in Iran. By noticing the evaluated factors, it is understandable that the climate factor has the intensive effect on desertification throughout the study region that they are out of control by human being.